2022
DOI: 10.1101/2022.01.26.477842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microliter spotting and micro-colony observation: a rapid and simple approach for counting bacterial colony forming units

Abstract: For enumerating viable bacteria, traditional dilution plating to count colony forming units (CFU) has always been the preferred method in microbiology owing to its simplicity, albeit laborious and time-consuming. Similar CFU counts can be obtained by quantifying growing microcolonies in conjunction with the perks of a microscope. Here, we employed a simple method of five microliter spotting of differently diluted bacterial culture multiples times on a single petri plate followed by finding out CFU by counting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…For quantitative analysis, sludge samples were vortexed for 3 mins to be completely homogenous, one mL of each sample was suspended separately in 9 mL of sterile saline, a series of decimal dilutions were prepared, 0.1 mL of each sample was plated on nutrient agar medium and incubated for 24 h at 37°C, total viable count (TVC) was expressed as colony forming units (cfu/mL) of the sample, experiments were undertaken in triplicates [21].…”
Section: Enumeration Of Total Bacterial Countsmentioning
confidence: 99%
“…For quantitative analysis, sludge samples were vortexed for 3 mins to be completely homogenous, one mL of each sample was suspended separately in 9 mL of sterile saline, a series of decimal dilutions were prepared, 0.1 mL of each sample was plated on nutrient agar medium and incubated for 24 h at 37°C, total viable count (TVC) was expressed as colony forming units (cfu/mL) of the sample, experiments were undertaken in triplicates [21].…”
Section: Enumeration Of Total Bacterial Countsmentioning
confidence: 99%
“…Although various studies reported about the twitching motility inR. solanacearum and the factors associated with it (Kai et al, 2015;Kang et al, 2002;Ray et al, 2015;Singh et al, 2018), its impact on the microcolony shape and size (Bhuyan et al 2023) in this bacterium in a density-dependent manner has not been reported yet. More importantly, the dynamics as well as the directionality of twitching motility exhibited by peripheral cells in a colony are yet to be studied adequately.…”
Section: Introductionmentioning
confidence: 98%
“…Although various studies reported about the twitching motility in R. solanacearum and the factors associated with it [13–15, 20], its impact on the microcolony shape [21] in this bacterium in a density‐dependent manner has not been reported yet. More importantly, the dynamics as well as the directionality of twitching motility exhibited by peripheral cells in a colony are yet to be studied adequately.…”
Section: Introductionmentioning
confidence: 99%